UNVEILING THE REALITIES OF ANAL MELANOMA CARE IN A RESOURCE-CONSTRAINED SETTING - Pragya Mitra,; Deepak Kumar,; Anju Khairwa,; Aneeket Modak, (Journal of Ayub Medical College Abbottabad, 2023)
A 50-year-old lady presented with complaints of a progressively increasing anal mass and occasional bleeding per rectum for the past 4 months. Examination revealed an ulcero-proliferative growth in the anal canal, whose biopsy was suggestive of malignant melanoma. Inguinal lymph nodes, though enlarged, did not show evidence of malignant deposits on FNAC. Radiological investigations revealed a T3 lesion with no evidence of nodal metastasis. She underwent local excision of the mass with uneventful intraoperative and postoperative periods. The purpose of this report is to highlight the formidable challenges encountered in diagnosing this rare tumour, with potential implications for misdiagnosis, particularly within a resource-poor setting. This case highlights the importance of resource-appropriate approaches and surgical options available in a tertiary care hospital in North India.